2010
DOI: 10.15517/rbt.v0i0.3405
|View full text |Cite
|
Sign up to set email alerts
|

Structure of mixed ombrophyllous forests with Araucaria angustifolia (Araucariaceae) under external stress in Southern Brazil

Abstract: This study is part of the Floristic and Forest inventory of Santa Catarina, conceived to evaluate forest resources, species composition and structure of forest remnants, providing information to update forest conservation and land use policy in Southern Brazilian State of Santa Catarina (95 000km²). in accordance to the Brazilian National Forest inventory (iFN-BR), the inventory applies systematic sampling, with 440 clusters containing four crosswise 1 000m² plots (20x50m) each, located on a 10x10km grid overl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
23

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 25 publications
1
32
0
23
Order By: Relevance
“…In contrast, practices that include the presence of livestock are clearly damaging to the regeneration of both A. araucana (Sanguinetti 2008, Parque Nacional Lanín 2011 and A. angustifolia (Vibrans et al 2011). …”
Section: Cultural Landscapes With Araucaria and Conservation By Use Pmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, practices that include the presence of livestock are clearly damaging to the regeneration of both A. araucana (Sanguinetti 2008, Parque Nacional Lanín 2011 and A. angustifolia (Vibrans et al 2011). …”
Section: Cultural Landscapes With Araucaria and Conservation By Use Pmentioning
confidence: 99%
“…Furthermore, according to Vibrans et al (2011), these remnant populations are found in areas with high levels of degradation and fragmentation. Although the species is present in 72 conservation units, this represents only 0.62% of their distribution area (Indrusiak and Monteiro 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Catarina (IFFSC), publicados por Vibrans et al (2011), mostram que 50% dos remanescentes amostrados da floresta ombrófila mista estão em estágio médio de regeneração e bastante degradados, que 45% dos fragmentos da vegetação estão em estágio avançado de sucessão e que apenas 5% dos remanescentes constituem florestas maduras ou primárias.…”
Section: Dados Do Inventário Florístico Florestal De Santaunclassified
“…For parana-pine, for example, the araucaria nut market is an alternative to the traditional wood use market, which greatly benefits the ecosystem and the conservation of this species' role in the market. It is notorious the need for incentives for activities aiming at the sustainable use of Araucaria forest resources (VIBRANS et al, 2011). Moreover, the lack of technical knowledge on forest resources is one of the reasons for the common replacement of native resources by resources from exotic species (SIMINSKI; FANTINI, 2010).…”
Section: Introductionmentioning
confidence: 99%